2018
DOI: 10.1037/xap0000149
|View full text |Cite
|
Sign up to set email alerts
|

It can become 5 °C warmer: The extremity effect in climate forecasts.

Abstract: Climate projections and other predictions are often described as outcomes that can happen, indicating possibilities that are imaginable, but uncertain. Whereas the meanings of other uncertainty terms have been extensively studied, the uses of modal verbs like can and will have rarely been examined. Participants in five experiments were shown graphs and verbal statements showing projections of future global warming, sea level rise, and other climate-related issues. All studies gave support for the extremity hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
(66 reference statements)
1
12
2
Order By: Relevance
“…Assimilative comparisons will have the opposite effect, as terms like nearly , almost, or up to indicate that high values are reachable. Recent studies indicate a similar usage of statements about outcomes that can happen (Teigen, Filkukova, & Hohle, ). Such statements (“it can be 5 °C warmer”) typically point to the upper extreme of a distribution, while at the same time highlighting this value as a real, obtainable possibility.…”
Section: Discussionmentioning
confidence: 75%
“…Assimilative comparisons will have the opposite effect, as terms like nearly , almost, or up to indicate that high values are reachable. Recent studies indicate a similar usage of statements about outcomes that can happen (Teigen, Filkukova, & Hohle, ). Such statements (“it can be 5 °C warmer”) typically point to the upper extreme of a distribution, while at the same time highlighting this value as a real, obtainable possibility.…”
Section: Discussionmentioning
confidence: 75%
“…But it is hard to legislate natural language, and formal definitions of selected phrases may conflict with natural usage of the same expressions (Berry et al, 2003;Budescu et al, 2012). A recent line of research has shown that the "translation approach" (which probabilities correspond to a good chance) should be complemented with a "which outcome approach" (which outcomes are characterized as having a good chance) (Juanchich et al, 2013;Teigen et al, 2014). For instance, unlikely is commonly translated as corresponding to a 10-30% probability (Mastrandrea et al, 2010;Theil, 2002).…”
Section: Probability Estimates Are Frequently Exaggerated: Additivitymentioning
confidence: 99%
“…However, it turns out that outcomes described as unlikely are those that have never (hitherto) occurred, in other words values with a minimal (close to zero) probability of occurrence, mostly values beyond the top of the distribution. This phenomenon has been labelled an extremity effect (Jenkins et al, 2018; which still, due to their extremeness, have a relatively low probability of occurrence (Teigen, Filkuková and Hohle, 2018). As these terms are often "translated" to denote a medium probability (around 50%), a lack of understanding of the extremity effect can lead to serious miscommunications.…”
Section: Probability Estimates Are Frequently Exaggerated: Additivitymentioning
confidence: 99%
See 2 more Smart Citations